Good power : leading positive change in our lives, work, and world - Rometty, Ginni, 1957- (Ascent Audio, 2023)
One of the world's most respected leaders, former IBM CEO Ginni Rometty overcame childhood and financial struggles to embark on a groundbreaking career that took her from entry-level engineer to eight years as the first woman CEO of an iconic global company. Forty years in business and public advocacy taught Rometty the transformative power of leadership that blends authenticity, relationships, and curiosity with vision, rigor, and conviction. In her personable yet direct voice, Rometty reveals experiences that taught her how to orchestrate change for clients, companies, and communities. Her lessons and stories offer a blueprint for how we can all drive meaningful change in positive ways-a concept she calls "good power." The book begins with raw, vivid memories from Rometty's youth and early professional life as she reflects on the trauma and role models that influenced how she later thought about good power. Rometty then shares how she strived to use good power during her career and as a transformative CEO. Five principles-be in service of many stakeholders, build belief among skeptics, make tough choices, champion tech ethics and inclusion, be resilient-show how to navigate tension and build trust on the path to real change. She also shows how good power can scale to address urgent societal issues, even in our polarizing times